2002
DOI: 10.1038/417095a
|View full text |Cite
|
Sign up to set email alerts
|

HIV preferentially infects HIV-specific CD4+ T cells

Abstract: HIV infection is associated with the progressive loss of CD4(+) T cells through their destruction or decreased production. A central, yet unresolved issue of HIV disease is the mechanism for this loss, and in particular whether HIV-specific CD4(+) T cells are preferentially affected. Here we show that HIV-specific memory CD4(+) T cells in infected individuals contain more HIV viral DNA than other memory CD4(+) T cells, at all stages of HIV disease. Additionally, following viral rebound during interruption of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
874
4
18

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,137 publications
(932 citation statements)
references
References 32 publications
36
874
4
18
Order By: Relevance
“…The model is given by the following differential equations which describe the development of the cells over time. (1) The infected HIV-specific CD4 T cells are denoted by y, and free virus particles are denoted by v. The CD4 T cells are assumed to proliferate at a rate proportional to the amount of virus recognized (ryv). This proliferation is density dependent, limited by the so called carrying capacity, k. This means that as the number of infected CD4 T cells increases, the proliferation rate slows down.…”
Section: Basic Dynamics Of Autocatalytic Virus Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…The model is given by the following differential equations which describe the development of the cells over time. (1) The infected HIV-specific CD4 T cells are denoted by y, and free virus particles are denoted by v. The CD4 T cells are assumed to proliferate at a rate proportional to the amount of virus recognized (ryv). This proliferation is density dependent, limited by the so called carrying capacity, k. This means that as the number of infected CD4 T cells increases, the proliferation rate slows down.…”
Section: Basic Dynamics Of Autocatalytic Virus Spreadmentioning
confidence: 99%
“…On the other hand, CD4 T cells are also a central component which orchestrates the generation of specific immune responses through the delivery of help. Recent studies have shown that a significant proportion of HIV-specific CD4 T cells are infected by the virus, and that this specific population of T cells might be preferentially infected [1]. This has important implications for understanding the dynamics between HIV and immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the capacity of HIV-1-specific CD4 + T cells to proliferate and secrete IL-2, characteristics which are typically preserved only in long-term nonprogressors, are not always restored after initiation of therapy, particularly when this is delayed beyond acute infection [3][4][5][6]. Loss of function may result from preferential infection of virus-specific cells by HIV-1 [4, 7,8]. Enhancement of HIV-1-specific cellular responses by therapeutic vaccination in combination with fully suppressive antiretroviral therapy might be used to maintain HIV-1 control without continuous drug treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is likely that HIV-containing DC may present antigen to specific CD4 lymphocytes as well as transfer HIV to them, thus resulting in their death. There is strong evidence for selective depletion of HIV-specific CD4 lymphocytes [39,40] and this could be a key mechanism, but is yet to be proven. HIV infection markedly affects the function of CD4 lymphocytes even before inducing lysis or apoptosis.…”
mentioning
confidence: 99%